Iklan
Iklan

Jawaban:

Untuk jawaban dan penjelasannya ada di foto

maaf kalau ada yang salah

Iklan
Iklan

Jawab:

Penjelasan dengan langkah-langkah:

1. 3 ( x + 6 ) = x + 2
   3x + 18    = x + 2

          2x    =  -16

            x    =  -8

2. 6x - (2x - 9 ) = 11

   6x -2x + 9     = 11

                4x    = 2

                  x    = 1/2

3. 9x - 2(3x + 5 ) = 2

   9x - 6x - 10     = 2

                3x      = 12

                  x      =  4

4. 7 ( x - 1 ) = 4 ( x - 5 )

    7x - 7    = 4x - 20

            3x  =   -13

              x  =  -13/3

Iklan
Iklan